Antithrombin Deficiency and Thrombosis: A Wide Clinical Scenario Reported in a Single Institution - Marco-Rico A; Marco-Vera P (Journal of Blood Medicine, 2023)
Ana Marco-Rico,1,2 Pascual Marco-Vera2,3 1Hemostasis and Thrombosis Department, Hematology Service, University General Hospital Dr. Balmis, Alicante, Spain; 2Biomedical Research Institute (ISABIAL), Alicante, Spain; 3Clinical Medicine Department, Miguel Hernández University, Alicante, SpainCorrespondence: Ana Marco-Rico, Hemostasis and Thrombosis Department, Hematology Service, University General Hospital Dr. Balmis, Pintor Baeza Avenue, 12, Alicante, 03010, Spain, Tel +34 965913863, Fax +34 965913869, Email marco_anaric@gva.esAbstract: Congenital antithrombin (AT) deficiency represents the form of thrombophilia with the highest thrombotic risk. It is characterized by a heterogeneous clinical presentation, depending mostly on the family history of thrombosis and type of genetic mutation. Inherited AT deficiency promotes idiopathic thrombosis at an early age (even in the pediatric population) and at atypical sites. Therefore, a positive family background necessitates ruling out this high-risk thrombophilia at a young age. Studying first-degree relatives, even if they are asymptomatic, is essential to establish thromboprophylaxis and a proper therapeutic approach in case of thrombosis. Patients with congenital AT deficiency require indefinite anticoagulation owing to the high thrombotic recurrence rate. Here, we present four unrelated cases reported in our institution who were diagnosed with hereditary AT deficiency, with a contrasting clinical evolution.Keywords: hereditary antithrombin deficiency, thrombosis, anticoagulation, heparin resistance, SERPINC1 gene mutation